1993
DOI: 10.1002/ajmg.1320470603
|View full text |Cite
|
Sign up to set email alerts
|

Tetrasomy 9p: Tissue‐limited idic(9p) in a child with mild manifestations and a normal CVS result. Report and review

Abstract: Supernumerary isochromosomes resulting in autosomal tetrasomy are rare and have been described only for 12p, 18p, and 9p. Nineteen previous cases of tetrasomy 9p have been reported, and in 6 cases, tissue-specific mosaicism was implied with the i(9p) cell line present exclusively or predominantly in blood. We report on an infant who had apparently normal chromosomes (46,XY) on CVS. He was referred for genetic evaluation because of mild developmental delay and minor anomalies. In 75% of blood cells he had an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 14 publications
0
41
1
2
Order By: Relevance
“…5 Tetrasomy 9p mosaicism commonly leads to facial dysmorphy associated with moderate to severe mental disability, mild growth retardation, renal and skeletal abnormalities, and congenital heart disease. However, normal phenotypes are also possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Tetrasomy 9p mosaicism commonly leads to facial dysmorphy associated with moderate to severe mental disability, mild growth retardation, renal and skeletal abnormalities, and congenital heart disease. However, normal phenotypes are also possible.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These include a number of so-called type I interferonopathies, 3 which are Mendelian diseases associated with a primary upregulation of type I interferon (IFN), a key cytokine in SLE and some IM pathophysiology. 4 Herein, we report for the first time that mosaic forms of tetrasomy 9p 5 can predispose to the development of overlap myositis associated with type I IFN upregulation.…”
mentioning
confidence: 87%
“…A wide variation in phenotype has been reported in the literature in association with tetrasomy 9p, ranging from mild developmental delay [9] to lethal malformations [3] . It has been suggested that clinical fi ndings may be infl uenced by 3 cytogenetic parameters, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…17 True mosaic trisomy 2, 5, 16, and 22 have also been described. 18 All reported cases of Pallister-Killian syndrome have occurred sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…The fibroblast cultures were fed in media after 4 days of initiation, after which they were monitored daily and harvested when the mitotic activity was sufficient to obtain suitable metaphase spreads for chromosomal analysis. Standard G-banding techniques revealed a mosaic karyotype, 47, XX, +i(12)(p10) [24]/48, XX, + +i(12)(p10) [7]/46, XX [17]. Tetrasomy for the short arm of chromosome 12 [ +i(12p)] was documented in half the cell population (24 of 48 cells) analysed, two supernumerary isochromosomes [ ++i(12p)] in seven cells, and a normal female karyotype in 17 cells (Figure 1).…”
Section: Perinatal/neonatal Case Presentationmentioning
confidence: 99%